Tumour in horseshoe kidney – different surgical treatment shown in five example cases - Tkocz, Michał; Kupajski, Maciej (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Horseshoe kidney is one of the most common genitourinary system anomalies. The frequency of its occurrence in the whole population is about 0.25%. In the available literature more than 200 cases of such tumour-defect coexistence have been described. Purpose of this study was to present the possibilities of using various methods of surgical treatment of tumors localized in the horseshoe kidney. Material and methods: In the years 2004–2007 five patients were diagnosed and treated for tumours in horseshoe kidneys. Ultrasonography, computed tomography, urography and nuclear magnetic resonance were applied in the diagnosis. During the treatment both open operations and modern methods of treating tumours with a diameter less than 40 mm (nephron sparing) were used. Results: Renal cell carcinoma (RCC) was confirmed in all the patients. Conclusions: Our observations confirm the fact that RCC is the most often diagnosed tumour in horseshoe kidneys. The prognostic factors are the same as in the case of tumours of the kidneys without any abnormalities. The diagnosis is based on applying the modern methods of imaging and in the treatment it is possible to apply the modern, non-invasive methods.